Barriers of Online Reading Learning Faced by College Students - Gesha Lailatul Fauziyyah; Alina Alina Lemieshevska; Lucky Rahayu Nurjamin; Asep Suparman (Institut Pendidikan Indonesia Garut, 2023)
In the online reading classroom, the learning activity is different from offline reading learning. It engages the internet and technology to read, comprehend, and learn new information. However, those skills perceive some barriers in the process of learning in students during online reading learning. This qualitative study examined the descriptions of the barriers in reading online learning in a college from students’ perspectives. This study was conducted in one of the private universities in West Java, Indonesia. The participants of this study were 7 college students and one reading lecturer. This study applied the interview and observation as the data collection. The finding of this study has resulted 5 barriers of online reading learning with some description for each barrier. Those barriers are; epistemological barriers, infrastructure barriers, attitudinal barriers, technical barriers, and financial barriers.